Rekonstruksi Pengaturan Tanggung Jawab Sosial dan Lingkungan Perseroan Terbatas Mendukung Sustainable Development Goals Berdasarkan Peraturan Pemerintah Nomor 47 Tahun 2012 - Ayuda Wisnu Anggoro; Albertus Sentot Sudarwanto (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
This study aims to examine and provide solutions to legal issues arising from TJSL regulations in Indonesia. In addition, this study aims to examine the reconstruction of TJSL regulations for limited liability companies in support of SDGs based on Government Regulation No. 47 of 2012. This research is a type of legal research. It analyzes the relationship between legal rules and recommends changes to deficiencies in regulations. This research is prescriptive in nature. It uses a legislative approach. In addition, this research uses a conceptual approach. Based on this research, it was found that legal issues arising from TJSL regulations in Indonesia exist in various aspects. There are various legal issues arising from TJSL regulations in Indonesia, such as inconsistency and fragmentation in regulations, unclear sanctions, and the absence of a special body or institution to oversee TJSL. The government, in this case the president, needs to reconstruct TJSL regulations by establishing a thematic TJSL program that integrates the 17 SDGs into the TJSL program. The reconstruction of TJSL regulations must be carried out in PP 47/2012 by establishing thematic TJSL programs to ensure the implementation of TJSL is targeted and supports the achievement of the SDGs.